Effects of salinity on the CO2 permeation across lipid bilayer for microalgae biofixation: A molecular dynamics study - Manrique, Robby (Animo Repository, 2018)
The continuous threat of increasing CO2 concentration in the atmosphere has altered the carbon balance of our planet causing global climate change. Biological fixation of atmospheric CO2 by unicellular microorganisms such as microalgae is a promising technology pursued extensively by researchers as a means for carbon capture. The study aimed to provide an atomic level of study that will demonstrate the effect of the salinity on the mechanism of CO2 absorption across microalgae lipid bilayer. Molecular dynamics simulations were utilized to calculate the free energies of CO2 molecule as it permeates inside the microalgae cell. In thermodynamics, the transport process of a molecule can be demonstrated through its free energy gradient. Thus, calculating the free energies of CO2 molecule across microalgae lipid bilayer can elucidate the mechanisms of permeation processes. Four microalgae lipid bilayer structures were constructed that contains 128-DPPC (dipalmitoylphosphatidylcholine) lipid bilayer with 3640 water molecules with different NaCl concentrations: 0, 3, 13, and 19 NaCl molecules which correspond to a salinity level of 0, 50, 200, and 300 mM, respectively. The cavity insertion Widom method was used to calculate the free energy of CO2 molecule along the lipid bilayer. The results demonstrated that the salinity does not affect the free energies significantly, thus, it does not hamper CO2 transport across microalgae lipid membrane. © 2017, Springer Science+Business Media Dordrecht.